Characterisation and thermodynamic calculations of biodegradable Mg–2.2Zn–3.7Ce and Mg–Ca–2.2Zn–3.7Ce alloys. Issue 11 (24th July 2017) - Bakhsheshi-Rad, H. R.; Hamzah, E.; Joy Yii, S. L.; Mostafa, A.; Ebrahimi-Kahrizsangi, R.; Medraj, M.
ABSTRACT: In the present study, the effect of Ca (0.5–6 wt-%) content on the microstructure, phase formation, and mechanical properties and in vitro degradation behaviour of Mg–2.2Zn–3.7Ce alloys were investigated. Microstructural analysis and thermodynamic calculations also showed that Mg–2.2Zn–3.7Ce alloy contain α-Mg, Mg12 Ce and CeMgZn2, while after adding 0.5 wt-% Ca to Mg–2.2Zn–3.7Ce alloy, IM1 (Ca3 Mg x Zn15− x ) (4.6 ≤ x ≤ 12) phase was detected. Further addition of Ca to 6 wt-% resulted in forming Mg2 Ca besides α-Mg, Mg12 Ce and IM1 with the absence of CeMgZn2 . The tensile strength and elongation of the Mg–Ca–2.2Zn–3.7Ce alloys increase with increasing Ca content up to 1.5 wt-%, while further addition of Ca to 6 wt-% has a reversed effect. Similarly, the degradation rate of the alloys increased first with increasing Ca content and then decreased.